2014
DOI: 10.1186/2050-6511-15-8
|View full text |Cite
|
Sign up to set email alerts
|

An outpatient antibacterial stewardship intervention during the journey to JCI accreditation

Abstract: BackgroundAntibacterial overuse, misuse and resistance have become a major global threat. The Joint Commission International (JCI) accreditation standards include quality improvement and patient safety, which is exemplified by antimicrobial stewardship. There are currently few reports on interventions to improve the quality of outpatient antibacterial prescribing.MethodsA before-after intervention study, aiming at antibacterial use in outpatients, was performed in a university-affiliated hospital with 2.8 mill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 23 publications
(21 reference statements)
0
22
0
3
Order By: Relevance
“…Key topics are related to implementation cost and expenditure after accreditation. On the one hand, accreditation could be an opportunity to increase funding (LEE, 2014) generating a positive impact on expenditures reduction (MERKOW et al, 2014;SONG;LI;ZHOU, 2014;LIU et al, 2015). For example, the one-year intervention program for outpatient antibacterial use during the journey to the JCI accreditation reduced the expenditure on antibacterial (SONG; LI; ZHOU, 2014).…”
Section: Financial Impacts Of Accreditationmentioning
confidence: 99%
See 4 more Smart Citations
“…Key topics are related to implementation cost and expenditure after accreditation. On the one hand, accreditation could be an opportunity to increase funding (LEE, 2014) generating a positive impact on expenditures reduction (MERKOW et al, 2014;SONG;LI;ZHOU, 2014;LIU et al, 2015). For example, the one-year intervention program for outpatient antibacterial use during the journey to the JCI accreditation reduced the expenditure on antibacterial (SONG; LI; ZHOU, 2014).…”
Section: Financial Impacts Of Accreditationmentioning
confidence: 99%
“…Nine studies examined patient outcomes (CHABANNON et al, 2012;BRODRIBB;KRUSKE;MILLER, 2013;GRATWOHL et al, 2014;MERKOW et al, 2014;NOUWENS et al, 2014;SONG;LI;ZHOU, 2014;TOWERS;CLARK, 2014;FALSTIE-JENSEN et al, 2015;TELEM et al, 2015), out of which six revealed positive associations between accreditation and patient outcome measures. For example, bariatric hospital accreditation improved patient outcomes as compared to unaccredited hospitals and within the same hospital compared to pre-accreditation (TELEM et al, 2015).…”
Section: Relationship To Quality Measuresmentioning
confidence: 99%
See 3 more Smart Citations